ECG Quiz 43 Question - Millar, Rob Scott; Chin, Ashley (SA Heart Journal, 2017)
<h4 style="margin: 0em 1em 0.25em 0em; padding-top: 0.75em; font-family: Georgia, ’Times New Roman’, Times, serif; font-weight: normal; font-size: 1.5em; color: #111111; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; letter-spacing: normal; orphans: 2; text-align: left; text-indent: 0px; text-transform: none; white-space: normal; widows: 2; word-spacing: 0px; -webkit-text-stroke-width: 0px; background-color: #fbfbf3;">ECG Quiz